Design and Implementation of an Offline-Capable Drone Tracking System for Agricultural Spraying Verification Using GPS and Multi-Level Water Tank Monitoring - Handri Santoso; Haryono (The Indonesian Journal of Computer Science, 2026)
Agricultural spraying drones have become an effective solution for increasing productivity and spraying uniformity in modern agriculture. However, landowners often face difficulties verifying whether spraying operations have actually been performed within designated areas. Conventional verification methods rely heavily on manual observation, which is labor-intensive, time-consuming, and prone to inaccuracies. This research presents the design and implementation of an offline-capable Drone Tracker system capable of recording drone operational activities through the integration of high-precision GPS tracking and multi-level water tank monitoring. The proposed system records location, speed, positioning quality, and tank liquid level every second, storing all information locally on an SD Card. Since agricultural areas frequently lack reliable internet connectivity, a store-and-forward synchronization mechanism is implemented, allowing data to be uploaded automatically once internet access becomes available. Experimental implementation demonstrates that the system can provide objective evidence of spraying activities while maintaining reliable operation in remote agricultural environments. The proposed solution improves transparency, accountability, and operational monitoring of agricultural drone services.